Basic accounting : made easy - Ballada, Win; Ballada, Susan (Manila : DomDane Publishers & Made Easy books, 2013)
This revised edition has fifteen chapters divided into four manageable study parts.
1. Accounting and its environment -- 2. About international accounting standards, New IFRS Framework -- 3. Accounting equation and the double entry system -- 4. Recording business transactions -- 5. Adjusting the accounts -- 6. Worksheet and financial statements -- 7. Completing the accounting cycle -- 8. Merchandising operations -- 9. Completing the cycle for a merchandising business -- 10. Special combination journals, and voucher system -- 11. Manufacturing operations -- 12. Internal control and cash -- 13. Accounts and notes receivable -- 14. Inventory, property and equipment -- 15. Payroll.
Keywords: ACCOUNTING